Avaliação do impacto de um incêndio de grandes proporções em um reservatório de água doce tropical (Represa do Lobo, Itirapina) - Giongo, Daniel Guido (Universidade Federal de São Carlos, 2025)
Wildfires are becoming increasingly frequent and intense due to climate change. The effects of fires on terrestrial ecosystems and the atmosphere are well documented, including the emission of gases and ash, as well as increased soil exposure to the elements. However, the impacts on aquatic environments remain poorly understood. The objective of this research is to assess changes in limnological parameters and the dynamics of planktonic communities in a tropical freshwater reservoir (Represa do Lobo, Itirapina) following a large-scale wildfire that occurred in September 2021. Data collected the day after the fire and during the subsequent four weeks were compared with a time series of 29 monthly samples taken before the fire and 26 monthly samples taken afterward. The central hypothesis is that the ash and residues from the fire caused changes in the aquatic environment, modifying limnological parameters, increasing nutrient availability, and altering the structure and functioning of planktonic communities. The fire immediately affected all variables, with most of them returning to their original patterns, while only four variables showed instability in the following years (turbidity, euphotic zone, Synechococcus and cladocerans abundance). Additionally, it was observed that the studied environment was spatially affected in a homogeneous manner, with only six variables (phytoplankton biomass, dissolved oxygen concentration, total phosphorus, humic-like organic matter, Synechococcus and cladocerans abundance) differing between the margin and center of the reservoir. Thus, it is concluded that the fire directly affected limnological factors and, consequently, planktonic communities, although most variables showed high resilience over time.
Assessment of the impact of a large-scale fire on a tropical freshwater reservoir (Lobo Reservoir, Itirapina)
Keywords: Fogo; Águas continentais; Limnologia; Nutrientes; Plâncton; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; 14. Vida na Água